The stability and accuracy of credit ratings - Carvalho, P.; Laux, P.; Pereira, J. (SSRN, 2014)
This paper investigates the motivations of Credit Rating Agencies (CRAs) to change their ratings, and the consequences of those changes. We propose a new measure of ratings stability that summarizes the information in a ratings transition matrix into a single scalar number. We find that the intensity with which CRAs change ratings varies through time. In particular, rating changes are more intense during economic bad times. Surprisingly, the periods of stronger rating changes are not associated with higher ratings accuracy. Instead, we find that rating changes are more intense in anticipation of higher corporate bond issuance. These results are consistent with CRAs positioning themselves as useful coordinators between firms and investors to facilitate efficient capital allocation.